МІСТО ЯК ОБ’ЄКТ ДОСЛІДЖЕННЯ В СУЧАСНОМУ НАУКОВОМУ ДИСКУРСІ СОЦІОЛОГІЇ ТА УРБАНІСТИКИ - Міхно Надія Костянтинівна (International Journal of Innovative Technologies in Social Science, 2020)
The main attention in this article is focused on outlining the dominant vectors of modern research on urban issues in sociological and urban discourses. Attention is paid to the peculiarities of the structuralist and constructivist directions of the analysis of the city. The urgency of applying the approach to the study of the textuality of urban space is emphasized. Some aspects of cultural-anthropological and network approaches to the study of the city are considered. The characteristic directions of researches of urban space within the limits of modern Ukrainian sociology and specifics of modern urban researches are outlined.